2001
DOI: 10.1063/1.1410888
|View full text |Cite
|
Sign up to set email alerts
|

InAs/GaSb-based lateral current injection laser

Abstract: We propose a contact structure for InAs/GaSb multilayers, such that electrons and holes are selectively injected in alternating layers. This enables the implementation of a far-infrared lateral current injection laser based on the InAs/GaSb superlattice. Preliminary calculation of the gain shows that both surface- and edge-emitting designs are possible.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2002
2002
2014
2014

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 65 publications
0
2
0
Order By: Relevance
“…High electron and hole density can thus be achieved without intentional doping, accompanied by high carrier mobility due to the absence of impurity scattering [11]. The unique electronic properties of the GaSb/InAs heterostructure have been used in development of a wide range of novel electronic and photonics devices such as high current density tunnel diodes [8,[12][13][14], tunnel field effect transistors (FETs) [15], infrared photodetectors [3], lasers [16], complementary metal-oxide −semiconductor FET [5,17] and frequency multipliers [18]. In a recent study, we reported on the electrical properties of radial GaSb/InAsSb junctions formed in core/shell nanowires (NWs), characterized using a two-probe configuration [10].…”
Section: Introductionmentioning
confidence: 99%
“…High electron and hole density can thus be achieved without intentional doping, accompanied by high carrier mobility due to the absence of impurity scattering [11]. The unique electronic properties of the GaSb/InAs heterostructure have been used in development of a wide range of novel electronic and photonics devices such as high current density tunnel diodes [8,[12][13][14], tunnel field effect transistors (FETs) [15], infrared photodetectors [3], lasers [16], complementary metal-oxide −semiconductor FET [5,17] and frequency multipliers [18]. In a recent study, we reported on the electrical properties of radial GaSb/InAsSb junctions formed in core/shell nanowires (NWs), characterized using a two-probe configuration [10].…”
Section: Introductionmentioning
confidence: 99%
“…Playing with the widths of InAs and GaSb wells it is possible to tune the separation between the ground electron level in InAs well (e1) and ground hole level in the GaSb well (hh1) from negative values of more than 100 meV to positive values of the same order of magnitude. That is, in principle, the separation between e1 and hh1 levels can be adjusted for generation of radiation from a few μm [15] to hundreds of μm (1 THz corresponds to 300 μm) and longer. [16] (ii) For wider quantum wells the initial overlap is not removed, but the hybridization gap is formed.…”
mentioning
confidence: 99%